Impact of microfinance on business income of SMEs in Malaysia - Mohd Ashhari, Zariyawati; Faizal, Diana Rose; Md Nassir, Annuar; Mokhtar, Suraya Hanim (2015)
Microfinance facilities in Malaysia began in 1987 with the establishment of Amanah Ikhtiar Malaysia (AIM). Due to the importance of Small Medium Enterprises (SME) in the country’s economic growth, Malaysia government has encouraged the involvement of more financial institutions in providing microcredit products to the public. Further, in 2006 the National SME Development Council (NSDC) approved a complete microfinance institutional framework proposed by Bank Negara Malaysia, comprising banking institutions, development financial institutions (DFIs) and credit cooperatives to generate a sustainable microfinance industry. Today, microfinance facilities are expected to bring vast impacts on development of SMEs in Malaysia. Therefore, the purpose of this study is to investigate the impact of microfinance facilities on business income of SMEs in Malaysia. Results show that microfinance brings essential effect toward business’ income of SMEs in Malaysia. SMEs has utilized the capital that they obtain from microfinance to improve their business.